DISPORA HOMO-SAPIENS BERBARISKAN MANUSIA PELAUT DI KEPULAUAN ASIA TENGGARA DAN LAHIRNYA TEORI MANUSIA KELUAR JAWA ( THEORY OUT OF JAVA-MAN) : SATU PEMIKIRAN DARI PERSPEKTIF KELAUTAN - Ismail Ali; Encep Supriatna (Jurnal Kemaritiman: Indonesian Journal of Maritime, 2023)
Traditionally, seas and oceans have become sources of inspiration in seeking the truth from facts to dispell the worldview of those who tended to asscoiate it with myths and superstitions. In fact, it is not far-fetched to suggest  that the change and development in present day Southeast Asia, from traditional kingdoms to modern nation-states are intimately rooted in and shaped by the contributions of our seafaring ancestors. History demonstrates how they risked as well as as sacrificed their lives crossing treacherous waters and encountering stormy weathers just to ensure their legacy and continuity of the future generations of seafarers, and turning this region into an epicentre of civilization that was second to none in the world of civilizations. Yet, their thousands of years of contributions and sacrifices appear trivial and paled to insignificance like ”shipwrecks laying at the bottom of the sea in their forgotten watery graves”. Based on several theories of the development of traditional civilizations in the Nusantara like the Out of Yunan and Out of Taiwan theories by western scholars, it appears that these theoretical paradigms have marginalized the realities of history, and therefore require to be ”straightened” via a Southeast Asia centric perspective. This writing is to revisit the salience of the ancient epoch and pre-historic man marked by the arrival of the homo-eractus  and homo-sapiens from mainland Asia to this region in the early journey and development of the history of maritime civilization; to explain how the seafaring communities  from the eras B.C. (Before Christ) to A.D. (Anno Domini)  were able to utilise seas and oceans as a source of emancipation and development, and eventual rise as feared and respected searfarers of the ancient world.